Propuesta de EcoBarrio aplicado al sector Víctor Emilio Valdivieso, Tierras Coloradas - Díaz Chávez, Diego Fernando (2018)
Abstract:The purpose of this work is to analyze the Victor Emilio Valdivieso neighborhood, "Tierras Coloradas", its natural, artificial and social resources, determining the principles and strategies of an Eco-neighborhood that can be executed. These strategies propose the responsible use of natural resources, the reduction of waste and the optimal use of public space, integrating the population in each of the stages of execution, and in the case of study, the neighborhood organization is the most Important they have. Currently, studies are carried out for the implementation of these strategies, and have already been awarded in sustainability contests developed in the city as is the case of the project Award "participatory Green Community" that won the second Place in the category "Repopulation, urban ornamentation and sustainable construction" of the Awards "SACHA" in 2017.